Social-Emotional Learning Workshop for Creating a Positive School Environment - Tarso; Saputra, Surya Adi; Suryatama, Handika (Indonesian Scientific Publication, 2024)
The objective of this activity is to ensure that participants understand and apply social and emotional learning based on mindfulness, with the goal of creating a school environment that supports both moral and intellectual development. Additionally, it is expected that participants will grasp educational values centered on tolerance, inclusivity, and respect for student rights, and will be capable of creating a comfortable environment for both students and teachers. The activity is conducted using an andragogical approach through the MERDEKA framework, which involves self-introspection, concept exploration, collaboration, contextual demonstration, and guided reflection. The participants are teachers and staff from Dr. Wahidin Senior High School, totaling 18 individuals. The event is held online via Google Meet, with a duration of 8 teaching hours. The final outcome of the activity is a plan for participants' self-management in leading instruction, along with policies and programs that respect student rights